Facebook as a tool for discursive resistance: a case study - Dehghan, Ehsan; Mohamad Ali, Afida (Malaysian Association of Modern Languages, 2016)
Iran is one of the few countries in the world with laws of compulsory hijab for women, regardless of their religion. In the last couple of years, Iranian women have formed online communities to resist such laws and voice their dissent. The role of online social networks in causing social change, and the extent to which these New Media can help the processes of emancipation and democratization has been a matter of increasing academic attention. However, there are not enough studies, particularly from a linguistics viewpoint, on the online resistance movement of Iranian women against compulsory hijab. This leaves a gap in our understanding of both the dynamics and strategies of such movements, and also the bigger question of whether or not New Media can be useful tools in advancing human rights, democracy, and equality. This study, employing the Discourse-Historical Approach to Critical Discourse Analysis, investigates a corpora of over 500 Facebook posts by the most popular pages created for the purpose of resisting compulsory hijab in Iran. In contrast to the dichotomization and Xenophobia reported in studies on similar discourses, our findings point to a trichotomized discourse, in which the Self is identified against a negatively represented domestic Other (Oikophobia), and a positively framed foreign Other (Xenophilia). The paper concludes that the use of New Media in this case has led to an illusion of resistance, and how the movement under study is self-destructive, reproducing the same ideologies it is resisting.